Incidencia del desempleo en el nivel de pobreza de los habitantes de la provincia de El Oro, periodo 2007-2017. - Valverde Fernandez, Gema Maria (My University, 2019)
Poverty is a problem that affects the quality of life of millions of inhabitants in an economy, its reduction being an important economic policy issue to be analyzed and discussed by government authorities. Therefore, the interest of this research work is focused on the analysis of the behavior of poverty measured in relation to unemployment, which is intended to determine by estimating a linear regression model applying ordinary least squares the incidence of unemployment and other control variables established to study the level of poverty of the inhabitants. In this sense, the methodology used in this research is the collection of data corresponding to the behavior of the variables poverty, unemployment, gross value added, public investment and migration of the country and the province of El Oro from 2007 to 2017, taking into account a descriptive, correlational-causal approach that allows to determine the incidence of each of the determined variables. Finally, through the results obtained, it is evident that the variables have contributed significantly in the explanation of the level of poverty in the province, in addition it is demonstrated that public investment is not a variable whose increase necessarily generates positive effects in the explanation of poverty.
La pobreza es un problema que afecta la calidad de vida de millones de habitantes en una economía, siendo su reducción un tema de política económica importante de analizar y discutir por las autoridades gubernamentales. Por ello el interés de este trabajo de investigación se centra en el análisis del comportamiento de la pobreza medido en relación al desempleo, el mismo que tiene como propósito determinar mediante la estimación de un modelo de regresión lineal aplicando mínimos cuadrados ordinarios la incidencia del desempleo y otras variables de control establecidas para estudiar el nivel de pobreza de los habitantes. En este sentido la metodología utilizada en esta investigación es la recolección de datos correspondientes al comportamiento de las variables pobreza, desempleo, valor agregado bruto, inversión pública y migración del país y la provincia de El Oro del periodo 2007 al 2017, tomando en cuenta un enfoque descriptivo, correlacional-causal que permite determinar la incidencia de cada una de las variables determinadas. Finalmente mediante los resultados obtenidos se evidencia que las variables han contribuido significativamente en la explicación del nivel de pobreza en la provincia, además se demuestra que la inversión pública no es una variable cuyo aumento necesariamente genera efectos positivos en la explicación de la pobreza.
Keywords: POBREZA; DESEMPLEO; VALOR AGREGADO BRUTO; INVERSIÓN PÚBLICA; MIGRACIÓN